Respuesta :
I think the correct answer from the choices listed above is the last option. To determine the answer, we substitute 3 and 10 to each choice and see whether the answer would equate to 0 for both values of x. We do as follows:
h(x) = x^2 – 13x – 30
h(3) = 3^2 – 13(3)– 30 = -60 <----------NOT ANSWER
h(x) = x2 – 7x – 30
h(3) = 3^2 – 7(3) – 30 = -42<----------NOT ANSWER
h(x) = 2x2 + 26x – 60
h(3) = 2(3)^2 + 26(3)– 60 = 36<----------NOT ANSWER
h(x) = 2x2 + 14x – 60
h(3) = 2(3)^2 + 14(3) – 60 = 0
h(-10) = 2(-10)^2 + 14(-10) – 60 = 0
h(x) = x^2 – 13x – 30
h(3) = 3^2 – 13(3)– 30 = -60 <----------NOT ANSWER
h(x) = x2 – 7x – 30
h(3) = 3^2 – 7(3) – 30 = -42<----------NOT ANSWER
h(x) = 2x2 + 26x – 60
h(3) = 2(3)^2 + 26(3)– 60 = 36<----------NOT ANSWER
h(x) = 2x2 + 14x – 60
h(3) = 2(3)^2 + 14(3) – 60 = 0
h(-10) = 2(-10)^2 + 14(-10) – 60 = 0